Fuzzy identification of the state of IT corporation - Goloskokov, Oleksandr Evgenovich; Drach, Tetjana Oleksandrivna; Shapoval, Serhii Evgenovich (НТУ "ХПИ", 2017)
The methods and approaches to solving the problem of corporate governance are analyzed. Economic, social-psychological, administrative methods of corporate management are considered. Situational, systemic, situational fuzzy approaches to corporate management are considered. It was decided to apply a situational fuzzy approach to solving the research problem. It is proposed to use the k-means clustering algorithm in order to distribute fuzzy situations by classes. Clustering problem is solved. The task of identifying the state of IT corporation. An example has been calculated with which you can conduct a comprehensive study of the state of the object, which allows you to get a full understanding of the estimated IT corporation not only at the time of the assessment, but also in the retrospective and forecast periods.

Проанализированы методы и подходы к решению задачи управления корпорацией. Рассмотрены экономические, социально-психологические, административные методы управления корпорацией. Рассмотрены ситуационный, системный, ситуационный нечеткий подходы к управлению корпорацией. Принято решение применять ситуационный нечеткий подход к решению задачи исследования. Предложено использовать алгоритм кластеризации k-средних для того, чтобы распределить нечеткие ситуации по классам. Решена задача кластеризации. Решена задача идентификации состояния ИТ корпорации.
Keywords: управление корпорацией; нечеткие ситуации; ситуационное нечеткое управление; corporate governance; fuzzy situations; situational fuzzy management